“Logic” of Social Destruction: Violence and Power - Jugović, Aleksandar; Simeunović-Patić, Biljana; Jugović, Jasenka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
In this paper, through three essays about the various manifestations of violence (violence against children in the institutions, violence in intimate relationships, sexual violence against children – case of pedophilia), start from the premise is that violence is a deliberately destructive action or abuse of power in the cultural value system or institutional environment that is at the informal tolerance to aggression and inequality. Social violence is a constant of our civilisation. Violence is happening in the interaction of individuals with other people, social structures, value systems and power relations. The conclusion is that it is the responsibility of the state, not only to provide good laws and their application, but also to clearly promote a non-violent general culture and a humanistic value system.